Usefulness of Stabilizer for Microanastomoses of Internal Thoracic Vessels during DIEP Flap Breast Reconstruction - Hamahata, Atsumori; Kubo, Kazuyuki; Matsumoto, Hiroshi; Yamaki, Takashi; Sakurai, Hiroyuki (Journal of Reconstructive Microsurgery Open, 2016)
Background Internal mammary arteries and veins are some of the most useful recipient vessels for autologous breast reconstruction. However, the internal mammary vessels are relatively small, which requires a high magnification power during microanastomoses, and respiratory fluctuations often disturb surgeons' focus on the vessels and affect performance of precise microanastomoses. Therefore, we developed a stabilizer for use during deep inferior epigastric artery perforator (DIEP) flap breast reconstructions.Methods From April 2013 to March 2015, 23 patients underwent DIEP flap breast reconstructions. In 15 of the patients (22 venous anastomoses, 15 arterial anastomoses), the microanastomoses were performed without the stabilizer. In eight of the patients (10 venous anastomoses, 8 arterial anastomoses), the microanastomoses were performed with the stabilizer. Times for each microanastomosis procedure (from the first suture to the last suture) were measured using retrospective intraoperative video in the two groups.Results All flaps survived without any microanastomosis problems. The average arterial microanastomosis times were 13 minutes 56 seconds (SD, 0 minute 53 seconds) in the stabilizer group and 15 minutes 25 seconds (SD, 4 minutes 11 seconds) in the nonstabilizer group (p < 0.05). The average venous microanastomosis times were 16 minutes 21 seconds (SD, 2 minutes 4 seconds) in the stabilizer group and 22 minutes 16 seconds (SD, 2 minutes 8 seconds) in the nonstabilizer group (p < 0.05).Conclusion We developed a stabilizer for microanastomosis of internal mammary vessels during DIEP flap breast reconstruction. The stabilizer significantly decreased the time of microanastomosis and reduced microsurgeons' stress.
Keywords: stabilizer; respiratory fluctuation; breast reconstruction